Elastoplastic Model Framework for Saturated Soils Subjected to a Freeze–Thaw Cycle Based on Generalized Plasticity Theory - Shengyi Cong (MDPI AG, 2021)
The failures of soil slopes during the construction of high-speed railway caused by the soil after the freeze–thaw (F–T) cycle and the subsequent threat to construction safety are critical issues. An appropriate constitutive model for soils accurately describing the deformation characteristics of soil slopes after the F–T cycle is very important. Few constitutive models of soils incorporate the F–T cycle, and the associated flow rule has always been employed in previous models, which results in an overestimation of the deformation of soil exposed to the F–T cycle. Generalized plasticity theory is widely used to predict the performance of geotechnical materials and is especially well adapted to deal with this type of generalized cyclic loading (such as a freeze–thaw cycle), and it overcomes the shortcomings of the associated flow rule that causes larger shear deformation. To this end, an elastoplastic model framework based on generalized plasticity theory with double yield surfaces for saturated soils subjected to F–T cycles was developed. Two types of plastic deformation mechanisms, i.e., plastic volumetric compression and plastic shear, were considered in this elastoplastic model. It was found that this model can accurately predict the mechanical behavior and deformation characteristics of saturated soils after F–T cycles.